Reliable calibration and validation of phenomenological and hybrid models of high-cell-density fed-batch cultures subject to metabolic overflow - Ibáñez, Francisco; Puentes-Cantor, Hernán; Bárzaga-Martell, Lisbel; Saa, Pedro A.; Agosin, Eduardo; Pérez-Correa, José Ricardo (Computers & chemical engineering, 2024)
Fed-batch cultures are the preferred operation mode for industrial bioprocesses requiring high cellular densities. Avoids accumulation of major fermentation by-products due to metabolic overflow, increasing process productivity. Reproducible operation at high cell densities is challenging (>100 gDCW/L), which has precluded rigorous model evaluation. Here, we evaluated three phenomenological models and proposed a novel hybrid model including a neural network. For this task, we generated highly reproducible fed-batch datasets of a recombinant yeast growing under oxidative, oxygen-limited, and respiro-fermentative metabolic regimes. The models were reliably calibrated using a systematic workflow based on pre-and post-regression diagnostics. Compared to the best-performing phenomenological model, the hybrid model substantially improved performance by 3.6- and 1.7-fold in the training and test data, respectively. This study illustrates how hybrid modeling approaches can advance our description of complex bioprocesses that could support more efficient operation strategies. •High-cell density fed-batch cultures were performed under different regimes.•Phenomenological models were calibrated and evaluated in different conditions.•Best performing model was expanded with a neural network model.•Hybrid model displayed superior accuracy for fitting training data and predicting test data.